2024
DOI: 10.3390/ma17051208
|View full text |Cite
|
Sign up to set email alerts
|

Marble Powder as a Soil Stabilizer: An Experimental Investigation of the Geotechnical Properties and Unconfined Compressive Strength Analysis

Ibrahim Haruna Umar,
Hang Lin

Abstract: Fine-grained soils present engineering challenges. Stabilization with marble powder has shown promise for improving engineering properties. Understanding the temporal evolution of Unconfined Compressive Strength (UCS) and geotechnical properties in stabilized soils could aid strength assessment. This study investigates the stabilization of fine-grained clayey soils using waste marble powder as an alternative binder. Laboratory experiments were conducted to evaluate the geotechnical properties of soil–marble po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
(81 reference statements)
1
5
0
Order By: Relevance
“…The existence of an ideal additive combination (6% cement + 6% sawdust ash in our case) yielding the lowest permeability values aligns with the work of Al-Tabbaa and Evans. They reported an optimum lime-GGBS proportion that maximized pozzolanic reactions and filler effects, thereby minimizing the flow potential in treated clays [78]. The reduced hydraulic conductivity values at moisture contents slightly wet of optimum are consistent with findings reported by several researchers investigating stabilized soils and compacted clay liners.…”
Section: Hydraulic Conductivitysupporting
confidence: 85%
See 2 more Smart Citations
“…The existence of an ideal additive combination (6% cement + 6% sawdust ash in our case) yielding the lowest permeability values aligns with the work of Al-Tabbaa and Evans. They reported an optimum lime-GGBS proportion that maximized pozzolanic reactions and filler effects, thereby minimizing the flow potential in treated clays [78]. The reduced hydraulic conductivity values at moisture contents slightly wet of optimum are consistent with findings reported by several researchers investigating stabilized soils and compacted clay liners.…”
Section: Hydraulic Conductivitysupporting
confidence: 85%
“…However, we acknowledge that a limitation of our study is the lack of microstructural investigations to elucidate the precise mechanisms behind the permeability trends observed. Future studies coupling hydraulic testing with techniques like SEM/XRD could provide deeper insights, as demonstrated by researchers like Mirzababaie et al working on natural pozzolan-amended clays [78].…”
Section: Anova Of Hydraulic Conductivity Against Water Contentmentioning
confidence: 96%
See 1 more Smart Citation
“…They showed that the optimal marble powder content for maximizing engineering effects is approximately 60% dry matter. CBR capacity ranges from 10.43% to 22.94% for unsoaked conditions and 4.68% to 12.46% for soaked conditions with 60% marble powder [14]. An experimental study made by Gallaego-Quintana to analyze the mechanical properties of a soil stabilized with ordinary Portland cement (OPC) under a sustainable approach consisting of a significant substitution of OPC for sugarcane bagasse ash (SCBA) to reduce the quantity of cement used in the stabilization shows that the 25% partial replacement of OPC by SCBA shows the best performance in its maximum dry density, reaching a compressive strength and California bearing ratio significantly close to the soil values with 100% OPC; this could imply, in practical terms, a reduction in cement consumption [15].…”
Section: Introductionmentioning
confidence: 99%
“…Predicting landslides remains a challenge in the fields of civil engineering, mining, and environmental protection because slope stability is of paramount importance [1][2][3][4][5][6][7][8][9][10][11]. The safety factor is a critical parameter in slope design.…”
Section: Introductionmentioning
confidence: 99%